Galectin-3 reflects the echocardiographic grades of left ventricular diastolic dysfunction - Ansari, Uzair; Behnes, Michael; Hoffmann, Julia; Natale, Michèle; Fastner, Christian; El-Battrawy, Ibrahim; Rusnak, Jonas; Kim, Seung‑Hyun; Lang, Siegfried; Hoffmann, Ursula; Bertsch, Thomas; Borggrefe, Martin; et al. (Annals of laboratory medicine, 2018)
Ansari U, et al. Ann Lab Med. 2018 Jul;38(4):306-315. https://doi.org/10.3343/alm.2018.38.4.306
Gesehen am 28.05.2020